Fishes of Taiwan and adjacent waters. - Warren Burgess & Herbert R. Axelrod ; in collaboration with Shih-chieh Shen. (Neptune City, New Jersey T.F.H. Publications, 1974)
Pacific marine fishes ; BK. 5
Keywords: Fishes--Taiwan--Identification.; Fishes--Taiwan.; Marine fishes--Taiwan--Identification.; Marine fishes--Taiwan.